2007
DOI: 10.1002/bjs.5707
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anastomotic leakage on oncological outcome after rectal cancer resection

Abstract: : A negative prognostic impact of anastomotic leakage on local recurrence and disease-free survival was found only for patients with leakage needing surgical revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
116
2
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(142 citation statements)
references
References 32 publications
9
116
2
11
Order By: Relevance
“…In general, the global, clinical judgement seems to localize a subset of patients at risk for developing complications in general, whereas many patients with no risk factors at all may develop anastomotic leakage [12]. The risk factors for anastomotic leakage identified by univariate and multivariate analysis in our study corroborate with those found in other studies [1][2][3][4][5][6][7][8]. Similar to these studies, the number of risk factors present in an individual patient appeared to be an important predictor of anastomotic leakage in all anastomoses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In general, the global, clinical judgement seems to localize a subset of patients at risk for developing complications in general, whereas many patients with no risk factors at all may develop anastomotic leakage [12]. The risk factors for anastomotic leakage identified by univariate and multivariate analysis in our study corroborate with those found in other studies [1][2][3][4][5][6][7][8]. Similar to these studies, the number of risk factors present in an individual patient appeared to be an important predictor of anastomotic leakage in all anastomoses.…”
Section: Discussionsupporting
confidence: 88%
“…Gastrointestinal anastomotic leakage causes increased early mortality [1] and, following potentially curative resection of colorectal cancer, leads to higher recurrence rates and a poorer oncologic prognosis [2]. Clinically relevant anastomotic leakage rates range between 3% and 19% [1,[3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Leakage can increase morbidity and mortality, prolong the duration of the hospital stay, and affect short-or long-term quality of life [7,8] . There is also evidence for an increased risk of local cancer recurrence and decreased long-term survival after leakage [9][10][11] . Many solutions have been sought to prevent or diminish anastomotic leakage, such as mechanical bowel preparation, drains, and intra-luminal devices.…”
Section: Introductionmentioning
confidence: 99%
“…Así, Bennis et al 23 , en pacientes con resección anterior baja y anastomosis coloanal, observaron que los pacientes de sexo masculino poseían un OR de 1,8 para morbilidad global y 2,3 para complicación médica. Por su parte, Ptok et al 24 , al analizar, sexo como factor de riesgo para filtración de anastomosis, encontraron que los pacientes de sexo masculino tenían una tasa de filtración más alta. Otros autores han encontrado resultados similares [25][26][27] .…”
unclassified
“…Entre ellos, las pérdidas de volumen sanguíneo, necesidad de transfusión, tiempo quirúrgico, uso de ileostomía, uso de drenajes, obesidad, tabaco, edad, drenaje transrectal, etc. [18][19][20][21][23][24][25] . Entre estos, el score de ASA es uno de los factores que se menciona sistemáticamente como factor de riesgo 18,19 lo que es concordante con lo observado en este estudio.…”
unclassified